RANCANG BANGUN APLIKASI PERHITUNGAN DAN PEMBAYARAN ZAKAT BERBASIS ANDROID (Universitas Palangka Raya, 2017)
Tithe is worship in treasure for moslems that has social value. However, sometime society find it difficult and forget to do because society is less familiar about any property that must be paid, the rules and calculations of tithe in Islam. Sometime society are confused and do not know where to pay the tithe. Application of tithe Calculation and payment based on android is the implementation of mobile smarthphone technology that is currently used by various circles. This application is expected can solve these problems. Application of tithe calculation and payment based on android had designed by Luther-Sutopo software development methods, that has six steps: (1) concept, (2) design, (3) material collecting, (4) assembly, (5) testing and (6) distribution. Implementation of the application had developed by Java programming for client (android) and web programming for server (website). Testing of the application used Blackbox Testing methods. Testing results based on questionnaires. After tests have done, the results are suitable with the expected conditions and comply the goals. For the future work, some features can be added to the application such as donatur member, object of tithe, then tithe calculator and donation for website.